(untitled) (Revue D’études Interculturelles De L’image, 2014)
Andres Veiel’s 2001 documentary film, Black Box BRD, links the biography of Alfred Herrhausen, RAF victim, with one of the 3rdgeneration RAF terrorists, Wolfgang Grams. In my paper, I trace how the film’s aesthetics introduce an image montage of two life scenarios by establishing both parallels and contrast, and therefore, following Susan Haywards definition “creates a third meaning” (112). I examine how the film establishes an aesthetic concept of Aussteigen (getting out)—along of the alive, visible bodies—the contemporary interviewees, and dead, invisible bodies—of Herrhausen and Grams.